2015
DOI: 10.3904/kjim.2015.30.5.602
|View full text |Cite
|
Sign up to set email alerts
|

Oral udenafil and aceclofenac for the prevention of post-endoscopic retrograde cholangiopancreatography pancreatitis in high-risk patients: a randomized multicenter study

Abstract: Background/Aims:Acute pancreatitis is a common complication of endoscopic retrograde cholangiopancreatography (ERCP). Combination therapy w ith ora l udenafil and aceclofenac may reduce the occurrence of post-ERCP pancreatitis by targeting different pathophysiological mechanisms. We investigated whether combining udenafil and aceclofenac reduced the rates of post-ERCP pancreatitis.Methods:A prospective, randomized, double-blind, placebo-controlled, multicenter study was conducted in four academic medical cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…They found no significant difference between rates of PEP incidence of two groups, indicating udenafil had no prophylactic impact on PEP. Lee et al[109] performed a prospective, randomized, double-blind, placebo-controlled, multicenter RCT to investigate the efficacy of a combination of a high dose of udenafil (PDE-5 inhibitor) and aceclofenac (NSAID) on development of PEP in high-risk patients. Their rationale for this study depended on the potential of the combination to decrease the pressure of the sphincter of Oddi and inflammation in acute pancreatitis through modulation of the cytokine cascade.…”
Section: Resultsmentioning
confidence: 99%
“…They found no significant difference between rates of PEP incidence of two groups, indicating udenafil had no prophylactic impact on PEP. Lee et al[109] performed a prospective, randomized, double-blind, placebo-controlled, multicenter RCT to investigate the efficacy of a combination of a high dose of udenafil (PDE-5 inhibitor) and aceclofenac (NSAID) on development of PEP in high-risk patients. Their rationale for this study depended on the potential of the combination to decrease the pressure of the sphincter of Oddi and inflammation in acute pancreatitis through modulation of the cytokine cascade.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to rectal suppositories, other routes of administration have also been studied. Oral diclofenac [30,31], celecoxib [32] or a combination of udenafil and aceclofenac [33] have not been found to reduce PEP compared to a placebo or saline infusion. Placebocontrolled studies have also found no significant difference in PEP rates with intravenous valdecoxib [34], or with the combination of intramuscular diclofenac and isotonic saline [35].…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 95%
“…Oral (two doses given 6 hours apart) [32,33] and intramuscular administration [34] of diclofenac have not shown a protective effect on PEP. Why are these methods of administration not effective in PEP prevention when the bioavailability is more than 90% in both instances?…”
Section: Why Only Rectal Nsaids Are Effective For Pepmentioning
confidence: 91%